2017
DOI: 10.1073/pnas.1613320114
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant silicateins as model biocatalysts in organosiloxane chemistry

Abstract: The family of silicatein enzymes from marine sponges (phylum Porifera) is unique in nature for catalyzing the formation of inorganic silica structures, which the organisms incorporate into their skeleton. However, the synthesis of organosiloxanes catalyzed by these enzymes has thus far remained largely unexplored. To investigate the reactivity of these enzymes in relation to this important class of compounds, their catalysis of Si-O bond hydrolysis and condensation was investigated with a range of model organo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(72 citation statements)
references
References 42 publications
5
49
1
Order By: Relevance
“…Müller et al . demonstrated that the same silicatein could interact with bulky bis(p-aminophenoxy)-dimethylsilane which contains two Si-O and two S-C bonds, that confirms that silicatein could interact not only with orthosilicic acid itself 10 , 16 . Besides that, silicateins possess directly confirmed proteolytic activity, which is hydrolytic too 17 19 .…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Müller et al . demonstrated that the same silicatein could interact with bulky bis(p-aminophenoxy)-dimethylsilane which contains two Si-O and two S-C bonds, that confirms that silicatein could interact not only with orthosilicic acid itself 10 , 16 . Besides that, silicateins possess directly confirmed proteolytic activity, which is hydrolytic too 17 19 .…”
Section: Discussionmentioning
confidence: 62%
“…Cysteine in the active site is supposed to be non-efficient for silica polymerization catalysis and is commonly described as a feature of cathepsins L 3 . Site-directed mutagenesis confirmed the crucial role of Ser26 and His165 in silicateins 7 , 10 .
Figure 1 Previously proposed mechanisms of the silicatein activity.
…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Two different approaches were used in this work, namely (1) DFT studies on enzyme active site models and (2) QM/MM calculations on a full enzymatic structure of a P450 isozyme. These QM/MM methods have been described in details elsewhere [ 55 , 56 , 62 , 63 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] and were extensively benchmarked and calibrated against experimental data. In particular, rate constants of small model complexes were reproduced excellently as compared to experimental data for oxygen atom transfer by iron (IV)-oxo and iron (IV)-imido species [ 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ].…”
Section: Methodsmentioning
confidence: 99%